COSMO–RS based prediction and screening of antimicrobial activities of deep eutectic solvents - Alafandi, Lama; Elgharbawy, Amal A.M.; Engku Ismail, Engku Normi (AIJR Publisher, 2023)
In this study, 18 various types of DESs were screened using COSMO–RS analysis, those DESs consisted of urea, thymol, menthol, and six different fatty acids. To be able to achieve the objective of this study which is to investigate the antimicrobial activity of the various DESs screened, the COSMO–RS analysis was conducted using 4 bacterial cell wall components (2,6-diaminopimelic-acid, N-Acetyl-a-neuraminic-acid, N_Acetyl_Muramic_acid, N_Acetyl_D_Glucosamine), to observe the interaction of the DESs with the bacterial cell. As a result, the σ-profiling and the σ-potential showed that the most interactive DESs against microbial cells were Decanoic acid based. The importance of this study is due to its time-resource saving in the screening of biochemical materials.